1064 Sleep Patterns Among Urban Haitian Earthquake Survivors Who Experienced the Trauma of Nonpartner Sexual Violence: A Latent Class Analysis Approach. (27th May 2020) - Rahill, G J; Joshi, M J; Blanc, J; Rice, C
Abstract: Introduction: Sleep health is crucial to recovery from trauma. Haiti's Cité Soleil residents (approximately 350, 000) live in extreme poverty and regularly experience or witness life-threatening events, including gang and non-partner sexual violence (NPSV). Differences in levels of sleep disturbance among men and women in resource-limited settings who survive disasters as well as NPSV are understudied. In a larger study in which we investigated trauma symptoms among 2010 Haiti earthquake survivors via the Trauma-symptom checklist -40 (N=526; 290 males, 236 females), we also assessed self-reported frequency of sleep disturbance symptoms using the measure's sleep disturbance subscale, comparing the latter by NPSV victim status and by gender. Methods: SAS enabled 3-Class Latent Class Analysis (LCA): Class 1 ("No symptoms"), Class 2 ("Some symptoms"), Class 3 ("All Symptoms)". Results: Distribution of class membership differed by gender (χ2 = 23.9, df = 2, p < .0001). Proportions of respondents assigned to the three classes differed between genders (Females: Class 1, 29.2%; Class 2, 35.5%; Class 3, 35.3%); Males: Class 1, 25.7%; Class 2, 54.4%; Class 3, 19.9%). NPSV status influenced levels of sleep disturbance symptoms, and membership distribution differed across classes by gender (χ2 = 23.9, df = 2, p < .0001). Class 2 membership was greater for men (65.9%), but class 3 membership was greater for women (59.3%). Women who experienced NPSV were statistically more likely members of sleep disturbance symptom classes (Class 2 or Class 3) than Class 1 (χ2= 14.9, df = 2, p = 0.0006). No difference was found in Class membership for men reporting NPSV (χ2= 1.6, df = 2, p = 0.45). Conclusion: Investigating the sleep health of Cité Soleil residents adds to the body of literature on sleep health, sleep equity and gendered vulnerability. Findings suggest women in post-disaster settings, especially in LMICs, are at even greater risk for a variety of adverse health outcomes and for suboptimal sleep, even when local men have similar traumatogenic experiences, such as NPSV. Girls and women in post-disaster LMIC settings need trauma-informed sleep health promotion and NPSV-prevention. Support: N/A